Philosophical Approaches In Interdisciplinary Studies Multicultural Islamic Education - Arikarani, Yesi; Lubis, Mawardi; Winarni, Indah; Qomarullah, Muhammad (El-Ghiroh : Jurnal Studi Keislaman, 2025)
This article discusses the philosophical approach in the interdisciplinary study of multicultural Islamic Education. Islam as a universal religion emphasizes human values, equal rights, and recognition of cultural diversity. In understanding multicultural Islam, philosophical approaches are an important instrument to explore the essence, essence, and wisdom of religious teachings. An interdisciplinary approach allows for the integration of various disciplines to provide a more comprehensive understanding of social, cultural, and religious issues. This research highlights how philosophical approaches are applied in Islamic studies through metaphysical, epistemological and axiological analyses. Using this perspective, Islam is not only understood in normative aspects but also in an applicative context that is relevant to the challenges of the times. The study also emphasizes the importance of multicultural Islamic education in building tolerance and harmony in a pluralistic society. The research uses qualitative methods through literature analysis. This research is analytical-descriptive, aiming to explore philosophical concepts, theories, and principles related to Islamic religious education in a multicultural context. Through this approach, research not only explains the concept, but also analyzes and interprets the meanings contained in it. This study concludes that a deeper understanding of Islam can be an alternative solution in dealing with social and cultural complexity. Multicultural Islamic education must continue to be developed as an effort to moderate religion to create an inclusive and peaceful society.